ANATOMY OF PLACE-MAKING IN THE CONTEXT OF THE COMMUNICATION PROCESSES: A STORY OF ONE COMMUNITY AND ONE SQUARE IN A POST-SOCIALIST CITY - Kotus, Jacek; Sowada, Tomasz; Rzeszewski, Michał; Mańkowska, Patrycja (Quaestiones Geographicae, 2019)
The article presents a discussion on the anatomy of place-making within the framework of the communication processes against the background of social order in a post-socialist city. The main aim of the text is to look at the social mechanisms of place-making processes “under the microscope”. The place-making activities are very often associated with planning and urban design. However, behind that planning veil is the social world of urban neighbourhood communities. In the article we propose, the social communication and participation processes are among the key factors responsible for creating urban spaces. We are presenting a place-making case study, using the example of Asnyk Square in Poznań. In this context, we are analysing social attitudes and social communication, which took place in the course of the place-making processes and influenced urban planning activities. The discussed case is complicated and provides no easy solutions.